2021
DOI: 10.1186/s12883-021-02473-5
|View full text |Cite
|
Sign up to set email alerts
|

Fasciculation differences between ALS and non-ALS patients: an ultrasound study

Abstract: Background Fasciculation is an important sign for the diagnosis of amyotrophic lateral sclerosis (ALS). Our study aimed to analyze the difference in fasciculation detected with muscle ultrasonography (MUS) between ALS patients and non-ALS patients with symptoms resembling ALS. Methods Eighty-eight ALS patients and fifty-four non-ALS (eight multifocal motor neuropathy, 32 chronic inflammatory demyelinating polyneuropathy/Charcot-Marie-Tooth, and 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 33 publications
0
11
2
3
Order By: Relevance
“…8,9 According to an intensity classification based on firing frequency and site number (Table ), the intensity of fasciculation in our patient before treatment with dantrolene was grade 4 (high grade). 10 A previous study suggested the intensity grading of fasciculation differs between ALS and non-ALS patients. 10 It is uncertain, however, whether grading fasciculation would provide diagnostic assistance in MH cases.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 According to an intensity classification based on firing frequency and site number (Table ), the intensity of fasciculation in our patient before treatment with dantrolene was grade 4 (high grade). 10 A previous study suggested the intensity grading of fasciculation differs between ALS and non-ALS patients. 10 It is uncertain, however, whether grading fasciculation would provide diagnostic assistance in MH cases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MU is useful for differentiating between ALS (a positive likelihood ratio of 6.17) and non-ALS patients (a negative likelihood ratio of 0.04) [ 14 ]. The fasciculation grade, assessed by MU, was higher in ALS patients than in non-ALS patients, and the distribution pattern was more easily detected in the proximal limbs of ALS patients [ 15 ]. Several MU findings, such as the extent and frequency of fasciculations, the decrease in muscle thickness, and the increase in echogenicity, are useful for estimating ALS progression and prognosis [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…der Zunge, 2: beidseitige Faszikulationen) bei einem Cut-Off-Wert von 3 eine Sensitivität von 86 % und eine Spezifität von 96 % sowie ähnliche Testgütekriterien in einer Validierungskohorte mit späterem ALS-Stadium [31]. Ähnliche Ergebnisse erbrachte die Anwendung eines 5-stufigen semiquantitativen Scores, in den für jeden analysierten Muskel sowohl Frequenz als auch örtliche Verteilung der Faszikulationen einging [32]. Es bleibt anzumerken, dass in keiner der Arbeiten nähere Angaben zu Untersuchungsdauer und -lokalisation der "nach klinischem Standard" durchgeführten Nadel-EMG-Untersuchung gemacht wurden, jedoch war die absolute Zahl der mit EMG untersuchten Muskeln angesichts der höheren Invasivität maximal gleich bzw.…”
Section: Sensitivität Und Spezifität Der Muskel-sonographieunclassified